KAJIAN KERENTANAN AIRTANAH TERHADAP PENCEMARAN DI DAERAH KARST GUNUNGSEWU (Studi di Daerah Aliran Sungai Bawah Tanah Bribin Kabupaten Gunungkidul dan Wonogiri) - , MARGARETHA WIDYASTUTI, DRA.,MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Karst groundwater is one of the potential natural resources in the Gunung Sewu karst area. On the other hand, karst aquifers are highly vulnerable to contamination. The research is conducted in catchment area of Bribin underground river that became the main source of water for the community, especially to support the water demand in the dry season. The purposes of this study are: 1) to analyze the spatial distribution of groundwater vulnerability to contamination variables (overlaying layer, the concentration of flow, rainfall), 2) to analyze the spatial distribution of groundwater vulnerability to contamination, and to validate the results of the groundwater vulnerability level to contamination, 3) to determine the factors that affect the vulnerability of groundwater level to contamination, 4) to evaluate the suitability of the COP method for the study area. The method of research was conducted by survey methods, through direct field measurements and survey of secondary data. Swallow holes, caves and doline were identified by census, while soils sampling were conducted by purposive sampling using soil series unit and consider the lithology formation and landform. The data processing method based on COP method, which is an acronym of C (concentration of flow), O (overlaying layer) and P (precipitation). Each variable and sub-variable has a value at each class, and then performed with the operation of multiplication and addition. The analysis unit used sinkhole recharge area and also underground river catchment area. The result of groundwater vulnerability to contamination class is indicated by COP index, which further were validated using hydrograph, chemograph and tracer tests. To determine the suitability of the COP method in the study area, the variables of C factor were tested statistically using factor analysis. The test results further were applied to assess the groundwater vulnerability to contamination using the COP method modification. The results show the spatial distribution of the variable of groundwater vulnerability to contamination varies. Concentration of flow (C) dominantly shows very high vulnerability values, whereas overlaying layer (O) include medium and high protection value (low and moderate vulnerability) and Precipitation (P) mostly show low vulnerability values. The level of vulnerability of groundwater to contamination leads to high and very high class which covered 63,04% areas. This is in line with the results of validation using a flow hydrograph, chemograph and tracer tests that show the quick response of groundwater quality, groundwater flow to the rainfall events or tracer substance. The factors that influences the level of groundwater vulnerability to contamination in the research area is concentration of flow (C). This condition is affected by by the number of sinkholes as point recharge of surface flow accumulation enters the groundwater system. Based on the condition of the study area, the sinkholes recharge area can replace the distance to the sinkholes variable. It can be proved by the level of groundwater vulnerability using Gunungsewu method give accurate result compared with previous COP method. Gunungsewu method can be applied in karst areas that have a diversity of enclosed basin conditions. Keywords: groundwater vulnerability, contamination, COP method, Gunungsewu method